Niche and interspecific associations of dominant tree species in Castanopsis eyrei and Castanopsis carlesii communities in Meihua Mountain, Fujian - Yu, Jiali; Chi, Mengwei; Gong, Chenyu; Chang, Menglin; He, Xing; Chen, Shipin; Wu, Jinping; Ma, Liang; Lan, Siren (Frontiers in Plant Science, 2026)
IntroductionSpecies composition, interspecific associations, and community stability play crucial roles in shaping individual plant survival and population dynamics. Research in this area carries multidimensional significance for forest conservation, contributing to the maintenance of ecological balance and the enhancement of biodiversity. To explore interspecific interactions among dominant species in evergreen broad-leaved forest communities and promote favorable community development, we selected two representative communities dominated by Castanopsis eyrei and Castanopsis carlesii for detailed investigation.MethodsUsing methods such as niche analysis, variance ratio (VR), chi-square test (χ²), and Spearman’s rank correlation, we analyzed the niche characteristics and interspecific association patterns of the 13 tree species with the highest importance values (IV) in each community.ResultsOur results revealed high species richness, with Castanopsis carlesii exhibiting the highest importance value and a relatively wide niche breadth, confirming its dominant role. However, the ranking of niche breadth did not correspond directly to the importance value ranking, suggesting that species distribution frequency plays a key role in determining niche width. The average niche overlap (0.26) and niche similarity coefficient (0.29) among dominant species were low, indicating limited resource sharing. Overall, interspecific associations showed a non-significant negative trend, both χ² and Spearman’s tests positive-to-negative association ratio was 0.77.DiscussionContrary to previous studies that suggest relative stability in evergreen broad-leaved forests, our findings indicate that the studied communities are currently in a relatively unstable developmental stage. This instability highlights the need for strategic adjustments in species composition and enhanced promotion of positive interspecific relationships. We therefore recommend deliberate optimization of tree species assemblages to strengthen facilitative interactions and improve community resilience.